2021
DOI: 10.1007/s10502-021-09366-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk in trustworthy digital repository audit and certification

Abstract: Risk is a foundational concept in digital preservation. While it has been examined from technical, economic, and organizational perspectives, I argue that it is also a social phenomenon. In this study I report on the results from 42 interviews with stakeholders in the Trustworthy Repositories Audit & Certification (TRAC) system, and analysis of documents relating to the ISO 16363 standard in order to examine how standard developers, auditors, and repository staff members understand the concept of risk for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Immunosenescence is characterized by the inability to mount effective [protective] humoral and cellular immune responses against a pathogen or vaccine, as well as a systemic low-grade inflammatory state [termed "inflammaging"], which contributes to the dysregulation of several components of " the innate and adaptive immune systems [87]. Much can be achieved, "when the science, engineering and health communities embrace human rights as an area suitable for and deserving of robust inquiry, and become an influential voice in the defense of human rights [88].…”
Section: Discussionmentioning
confidence: 99%
“…Immunosenescence is characterized by the inability to mount effective [protective] humoral and cellular immune responses against a pathogen or vaccine, as well as a systemic low-grade inflammatory state [termed "inflammaging"], which contributes to the dysregulation of several components of " the innate and adaptive immune systems [87]. Much can be achieved, "when the science, engineering and health communities embrace human rights as an area suitable for and deserving of robust inquiry, and become an influential voice in the defense of human rights [88].…”
Section: Discussionmentioning
confidence: 99%
“…Through TRAC certification, repositories demonstrate their trustworthiness regarding the long-term preservation of digital information. In order to do so, they show documentary evidence of risk assessment and mitigation efforts, which is reviewed by external auditors (Frank, 2022). The ISO 16363 standard states:A trustworthy digital repository will understand threats to and risks within its systems.…”
Section: Background/literature Reviewmentioning
confidence: 99%
“…TRAC was a joint effort by CRL, the Research Libraries Group (RLG), the National Archives and Records administration (NARA), and the Consultative Committee for Space Data Systems (CCSDS) (Yakel, 2007) Through TRAC certification, repositories demonstrate their trustworthiness regarding the long-term preservation of digital information. In order to do so, they show documentary evidence of risk assessment and mitigation efforts, which is reviewed by external auditors (Frank, 2022). The ISO 16363 standard states:…”
Section: Risk In Trustworthy Digital Repository Audit and Certificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finance has been identified as one of the major risks affecting digital preservation due to uncertainty about funding sources and the lack of stable long-term funding. 61 The study found the IRs had currently invested in hardware and software, with all three IRs utilizing the dSPACE platform. Rosa et al, 62 described dSPACE as software created with digital preservation in mind that allows repositories to perform all the functions outlined in the OAIS reference model.…”
Section: Budgeting Done Overall For the Librarymentioning
confidence: 99%